If there is an evolutionary selection pressure for the high frequency of MBL2 polymorphisms, what is it?. (May 2014) - Eisen, D. P.; Osthoff, M.
Summary Either immune selection or stochastic processes may have influenced the frequency of highly polymorphic genes such as mannose‐binding lectin 2 (MBL2). This pattern recognition receptor of the innate immune system recognizes and binds to pathogenic microorganisms and apoptotic cells leading to lectin pathway complement killing or clearance. In almost all of a large number of studies in different ethnic groups worldwide there is 20–25% carriage of low MBL2 haplotypes, with 8–10% of each population having no MBL detectable in the blood. The source of this high variability of MBL2 remains cryptic. It arises from six main snps in the prompter and exon regions of the gene that assort into seven common haplotypes under linkage disequilibrium. While global studies of MBL2 show that it is not under immune selection pressure, these results are not the same when the same population genetic tools are used on large national studies. Other analyses point to the silenced MBL1 pseudogene and development of promoter polymorphisms in humans as evidence of selection pressure favouring low‐producing haplotypes. While these analyses cannot be reconciled readily, there are two processes by which MBL heterozygosity could have been advantageous in an evolutionary sense; protection against adverse effects of various infectious diseases and lethal manifestations of atherosclerosis – a disease that now seems to have a more ancient history than assumed previously. Ultimately, consideration of the context for possible future therapeutic manipulation of MBL means that this can proceed independently of resolution of the evolutionary forces that have shaped MBL2 polymorphism.